Oxygen tension affects histone remodeling of in vitro-produced embryos in a bovine model - Gaspar, Roberta C. [UNESP]; Arnold, Daniel R.; Correa, Carolina A. P. [UNESP]; Rocha, Carlos V. da [UNESP]; Penteado, Joao C. T. [UNESP]; del Collado, Maite [UNESP]; Vantini, Roberta [UNESP]; Garcia, Joaquim M. [UNESP]; Lopes, Flavia L. [UNESP] (Elsevier B.V., 2015)
In vitro production of bovine embryos is a biotechnology of great economic impact. Epigenetic processes, such as histone remodeling, control gene expression and are essential for proper embryo development. Given the importance of IVP as a reproductive biotechnology, the role of epigenetic processes during embryo development, and the important correlation between culture conditions and epigenetic patterns, the present study was designed as a 2 x 2 factorial to investigate the influence of varying oxygen tensions (O-2; 5% and 20%) and concentrations of fetal bovine serum (0% and 2.5%), during IVC, in the epigenetic remodeling of H3K9me2 (repressive) and H3K4me2 (permissive) in bovine embryos. Bovine oocytes were used for IVP of embryos, cleavage and blastocyst rates were evaluated, and expanded blastocysts were used for evaluation of the histone marks H3K9me2 and H3K4me2. Morulae and expanded blastocysts were also used to evaluate the expression of remodeling enzymes, specific to the aforementioned marks, by real-time polymerase chain reaction. Embryos produced in the presence of fetal bovine serum (2.5%) had a 10% higher rate of blastocyst formation. Global staining for the residues H3K9me2 and H3K4me2 was not affected significantly by the presence of serum. Notwithstanding, the main effect of oxygen tension was significant for both histone marks, with both repressive and permissive marks being higher in embryos cultured at the higher oxygen tension; however, expression of the remodeling enzymes did not differ in morulae or blastocysts in response to the varying oxygen tension. These results suggest that the use of serum during IVC of embryos increases blastocyst rate without affecting the evaluated histone marks and that oxygen tension has an important effect on the histone marks H3K9me2 and H3K4me2 in bovine blastocysts.
Keywords: Embryo; Histone; IVF; H3K9me2; H3K4me2; Oxygen tension